miR-10b and miR-223-3p in serum microvesicles signal progression from prediabetes to type 2 diabetes - Parrizas, M.; Mundet, X.; Castaño, C.; Canivell, S.; Cos, X.; Brugnara, L.; Giráldez-García, C.; Regidor, E.; Mata-Cases, M.; Franch-Nadal, J.; Novials, A. (Journal of endocrinological investigation, 2020)
Purpose Type 2 diabetes frequently remains undiagnosed for years, whereas early detection of affected individuals would facilitate the implementation of timely and cost-effective therapies, hence decreasing morbidity. With the intention of identifying novel diagnostic biomarkers, we characterized the miRNA profile of microvesicles isolated from retroactive serum samples of normoglycemic individuals and two groups of subjects with prediabetes that in the following 4 years either progressed to overt diabetes or remained stable. Methods We profiled miRNAs in serum microvesicles of a selected group of control and prediabetic individuals participating in the PREDAPS cohort study. Half of the subjects with prediabetes were diagnosed with diabetes during the 4 years of follow-up, while the glycemic status of the other half remained unchanged. Results We identified two miRNAs, miR - 10b and miR - 223 - 3p , which target components of the insulin signaling pathway and whose ratio discriminates between these two subgroups of prediabetic individuals at a stage at which other features, including glycemia, are less proficient at separating them. In global, the profile of miRNAs in microvesicles of prediabetic subjects primed to progress to overt diabetes was more similar to that of diabetic patients than the profile of prediabetic subjects who did not progress. Conclusion We have identified a miRNA signature in serum microvesicles that can be used as a new screening biomarker to identify subjects with prediabetes at high risk of developing diabetes, hence allowing the implementation of earlier, and probably more effective, therapeutic interventions.